2011
DOI: 10.1111/j.1750-3841.2011.02403.x
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric Powder and Starch: Selected Physical, Physicochemical, and Microstructural Properties

Abstract: Isolation and characterization of starch from an unconventional source like turmeric rhizome indicate a potential application as a functional ingredient in foods and pharmaceutical industries including agglomerated products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 19 publications
2
27
2
Order By: Relevance
“…Starch is frequently isolated and is used in food industries to impart the desirable functional properties, and modify food texture and consistency [54].…”
Section: Non-conventional Sourcesmentioning
confidence: 99%
“…Starch is frequently isolated and is used in food industries to impart the desirable functional properties, and modify food texture and consistency [54].…”
Section: Non-conventional Sourcesmentioning
confidence: 99%
“…Thus, our finding may reinforce the evidence that turmeric starch is even more resistant to gelatinization (recalcitrant to digestion) when it is autoclaved. However, the degree of gelatinization seems to be different between the isolated starch and powder of turmeric depending on the presence of protein and crude fiber, [ 15 ] where turmeric fiber is known to trap starch and inhibit the access of water during the gelatinization process. [ 16 ] Yet, the observed phenomenon in this study is not specific only to turmeric powder, where it was observed that the starch particles from adzuki bean were also encapsulated by the denatured protein in the cooked adzuki bean paste similarly, [ 17 ] which showed RS characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…DOI: 10.13040/IJPSR.0975-8232.11 (11). This article can be accessed online on www.ijpsr.com DOI link: http://dx.doi.org/10.13040/IJPSR.0975-8232.11 (11).5712-17…”
Section: Quick Response Codementioning
confidence: 99%
“…The microstructure of the isolated starch sample was examined by employing a scanning electron microscope (SEM) previously used method by Dhanalakshmi, Kuttigounder. In the SEM analysis, the starch sample has interacted with some focussed beam of electronic energy, It scanned the sample and visualized its images on display 11 .…”
Section: Starch Morphological Analysis By Scanning Electron Microscopymentioning
confidence: 99%